PENGEMBANGAN MEDIA PEMBELAJARAN MENGGUNAKAN IPS MENGGUNAKAN GAME EDUKASI DI SEKOLAH - Yona Yolanda (PAKAR Pendidikan, 2018)
The study was designed : 1) Identify creative teaching materials. 2) Understanding of social science at Taluk elementary school, 3) formulating the concept of IPS by using educational games in elementary school as an effort to improve the quality of learning outcomes and characteristics of students. (4) increasing the creativity of teachers in attracting the students' attention to learn social science. Technique of collecting data is book review. The results of the data analysis show: (1) The purpose of social science develops the potential of students' attitudes, knowledge and skills in learning social knowledge (2) develops creative social knowledge with educational games in school one way teachers attract students to learn social knowledge.